Perlindungan Hukum Terhadap Pekerja Migran Indonesia Berdasarkan Peraturan Pemerintah Nomor 59 Tahun 2021: Studi Putusan Pengadilan Negeri Nomor 338/Pid.Sus/2021/PN.IDM - Mey Mawar Mona Rosanti; Ujang Charda; Sri Nurcahyani; Moh. Asep Suharna (CV. Ulil Albab Corp, 2024)
The government has mandated that every worker has equal employment rights and opportunities to choose, obtain, or change jobs and earn a decent income domestically or abroad. Despite the opportunities offered, working abroad also has its risks and challenges for migrant workers, such as exploitation, discrimination, unsafe working conditions, and legal and immigration issues. The aim to be achieved in this research is to find out how legal protection is for Indonesian Migrant Workers based on Government Regulation Number 59 of 2021 concerning the Implementation of Protection for Indonesian Migrant Workers. The research method used is descriptive-analytical with a normative juridical approach through the library research stage with data collection techniques through secondary data. The lack of activity by the central and regional governments in formulating policies regarding the eradication of illegal Indonesian Migrant Worker Placement Companies is one of the causes of the problem in legal protection for Indonesian Migrant Workers.